PENGARUH LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN DI DAIMA HOTEL PADANG - Nadilla, Demarta (journal of residu, 2019)
This study aims to determine the effect of the work environment on employee job satisfaction at Daima Hotel Padang. This type of research is causal associative research using simple linear regression analysis. The population in this study were employees who were 59 people and the number of samples in this study amounted to 51 employees except the head of department with sampling techniques were saturated samples. Data collection techniques were carried out using a questionnaire with a Likert scale that had been tested for validity and reliability. Technical analysis uses the help of the SPSS Computer Program version 16.00. The results showed: (1) Work Environment is in good category (64.70%), (2) Job Satisfaction is in a very good category (68.63%), (3) Simple linear regression hypothesis test results obtained F count 16,172 with sig. 0,000 <0,05, then the work environment variable can explain the variable of employee job satisfaction significantly. Furthermore, t count is 4.021 with a significant level of 0.000 <0.05, then there is a significant relationship between the two variables. Then the value of R Square is 0.248. This means that the work environment affects employee employment by 24.8%.